PENGARUH PERLAKUAN AWAL TERHADAP KARAKTERISTIK KIMIA DAN ORGANOLEPTIK TEPUNG JAMUR TIRAM (Pleurotus oestreatus) - -, Ardiansyah; Nurainy, Fibra; Astuti, Susi (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2014)
Oyster mushroom (Pleuorutus ostreatus) is one of healthy vegetables and widely consumed. Oyster mushroom is very perishable. When stored at cool temperatur, oyster mushroom only stands for 3-5 days, although it has been packed in polyethylene plastic bags. To extend its shelf life , oyster mushroom can be processed ​​into flour. This study was aimed to find the best treatment to produceoyster mushroom flour that has the best chemical and organoleptic properties. The experiment was arranged in a Completely Randomized Block Design with single factor and 4 replications. The single factor was consisted of six levels pretreatment : control, blanching, soaking in 0.5% citric acid for 10 minutes, blanching + soaking in 0.5% citric acid for 10 minutes, soaking in 2500 ppm sodium bisulphite for 10 minutes, and blanching + soaking in 2500 ppm sodium bisulphite for 10 minutes. The parameters observed : chemical characteristics (water, ash, protein, fat, carbohydrate contents) and organleptic property of color. ANOVA was used to analyse the data, and then continued using Honestly Significant Difference test (HSD) at 5% level of significance. The results showed that pretreatment significantly affected the moisture, fat, protein, ash, carbohydrate contents and color of oyster mushroom flour. The best oyster mushroom flour was found in the control flour (with no pre-treatment) with chemical characteristics: water content 7.29%, ash content 8.01%, protein content 17.50%, fat content 1,93% and carbohydrate content of 73.68%., and organoleptic characteristic of color was scored as white (4.3). Keywords :citric acid, blanching, flour, oyster mushroom, sodium bisulphite